Ankle Plantarflexor Spasticity Does Not Restrict the Recovery of Ankle Plantarflexor Strength or Ankle Power Generation for Push-Off During Walking Following Traumatic Brain Injury. Issue 4 (July 2016) - Williams, Gavin; Banky, Megan; Olver, John
Abstract : Objective: The main aim of this project was to determine the impact of plantarflexor spasticity on muscle performance for ambulant people with traumatic brain injury (TBI). Setting: A large metropolitan rehabilitation hospital. Participants: Seventy-two ambulant people with TBI who were attending physiotherapy for mobility limitations. Twenty-four participants returned for a 6-month follow-up reassessment. Design: Cross-sectional cohort study. Main Measures: Self-selected walking speed, Tardieu scale, ankle plantarflexor strength, and ankle power generation (APG). Results: Participants with ankle plantarflexor spasticity had significantly lower self-selected walking speed; however, there was no significant difference in ankle plantarflexor strength or APG. Participants with ankle plantarflexor spasticity were not restricted in the recovery of self-selected walking speed, ankle plantarflexor strength, or APG, indicating equivalent ability to improve their mobility over time despite the presence of spasticity. Conclusion: Following TBI, people with ankle plantarflexor spasticity have significantly greater mobility limitations than those without spasticity, yet retain the capacity for recovery of self-selected walking speed, ankle plantarflexor strength, and APG.